Identification of discriminant features from stationary pattern of nucleotide bases and their application to essential gene classification - Rout, Ranjeet Kumar; Umer, Saiyed; Khandelwal, Monika; Pati, Smitarani; Mallik, Saurav; Balabantaray, Bunil Kumar; Qin, Hong (Frontiers in Genetics, 2023)
Essential genes are essential for the survival of various species. These genes are a family linked to critical cellular activities for species survival. These genes are coded for proteins that regulate central metabolism, gene translation, deoxyribonucleic acid replication, and fundamental cellular structure and facilitate intracellular and extracellular transport. Essential genes preserve crucial genomics information that may hold the key to a detailed knowledge of life and evolution. Essential gene studies have long been regarded as a vital topic in computational biology due to their relevance. An essential gene is composed of adenine, guanine, cytosine, and thymine and its various combinations. This paper presents a novel method of extracting information on the stationary patterns of nucleotides such as adenine, guanine, cytosine, and thymine in each gene. For these purposes, some co-occurrence matrices are derived that brings the statistical distribution of stationary patterns of nucleotides in the genes, helpful in establishing the relationship between the nucleotides. For extracting discriminant features from each cooccurrence matrix, Energy, Entropy, Homogeneity, Contrast, and Dissimilarity features are computed, which are extracted from all co-occurrence matrices and then concatenated to form a feature vector representing each essential gene. Finally, supervised machine learning algorithms have been applied for essential gene classification based on the extracted fixed dimensional feature vectors. For comparison purposes, some existing state-of-the-art feature representation techniques such as Shannon entropy, Hurst exponent, fractal dimension and their combinations have been utilized. An extensive experiment has been performed for classifying essential genes of five species that show the robustness and effectiveness of the proposed methodology.